Induction of zinc particles on the morphology and photoluminescent property of globular Zn/ZnO core/shell nanorod heterojunction array architectures. Issue 5 (23rd March 2016) - Wang, Ziya; Wang, Fengping; Lu, Yanzhen; Xu, Mei; Li, Quanshui
Abstract : Zn/ZnO metal/semiconductor nanostructures were successfully synthesised by a facile zinc-rich chemistry liquid-phase approach with zinc microspheres as sacrificial templates at ambient temperature. A series of globular Zn/ZnO core/shell structures and hollow microsphere architectures self-assembled by Zn/ZnO nanorod heterojunction arrays were obtained by controlling the amount of zinc particles. The structure, morphology, composition and optical properties of the products have been characterised by X-ray diffraction, scanning electron microscopy, Raman spectroscopy and photoluminescent spectroscopy. A possible growth mechanism of the Zn/ZnO nanostructures has been proposed based on the structural analysis. The growth mechanism of Zn/ZnO hollow microspheres is ascribed to Kirkendall effect. A new strong blue emission at 440 nm and a green emission around 500 nm with an enhancement over one order of magnitude compared with the pure ZnO sample have been observed. These emission bands are attributed to two kinds of mechanisms that have been discussed in detail.